AKAD JUAL BELI DALAM PERSPEKTIF FIKIH DAN PRAKTIKNYA DI PASAR MODAL INDONESIA - Ab Mumin bin Ab Ghani, Eka Nuraini Rachmawati & (al-'adalah, 2015)
Abstract: Sales Contracts in the Perspective of Islamic Law and Their Practice in Indonesia Stock Market. This article reviews the perspective of Islamic law on a particular sale agreement (Bay Muzayadah, Bay wafa ‘and Bay istighlâl) and its implementation in the issuance of sukuk (certificate of compliance bond) both corporate and government bonds (SBSN). The discussion covers the types of sukuk, its legal basis, the issuance mechanisms, including the nature of ownership transfer. Generally, the issuance of corporate sukuk in Indonesia uses two types of contracts, namely Ijârah-using 12 structures of contracts-and Mudharabah-using 7 seven structures. Although the contract takes similar form, the structure may vary-depending on the type of business, the purposes, as well as the selection of the contracts.Keywords: sale and purchase of sukuk, stock marketAbstrak: Akad Jual Beli dalam Perspektif Fikih dan Praktiknya di Pasar Modal Indonesia. Artikel ini mengulas perspektif fikih terhadap akad jual beli (Bay muzayadah, Bay wafa’ dan Bay istighlâl) dan implementasinya dalam penerbitan sukuk, baik sukuk korporasi maupun sukuk negara (SBSN). Materi pembahasan meliputi jenis-jenis sukuk, landasan hukum, mekanisme penerbitan, termasuk bentuk pemindahan kepemilikan dari penerbit sukuk kepada investor apakah berupa pemindahan kepemilikan, kepemilikan hutang atau kepemilikan manfaat atas suatu aset. Dalam praktik, penerbitan sukuk korporasi di Indonesia hanya menggunakan dua jenis akad, yakni akad Ijârah-yang menggunakan 12 struktur akad-dan akad Mudhârabah-yang menggunakan tujuh struktur. Meski akadnya sama, tetapi ternyata strukturnya berbeda, tergantung pada jenis usaha emiten, tujuan penggunaan, serta pilihan akad pada saat penerbitan.Keywords: jual beli sukuk, pasar modal